Economic sustainability and methodological evaluation of air asset - Kumar Singh, Mahesh; Vásáry, Miklós; Baranyai, Zsolt (Studia Mundi – Economica, 2014)
Sustainability is focused on balancing environmental, economic and social concerns in order to “meet the needs of the present without compromising the ability of future generations to meet their own needs. Poor air quality threatens not only the well-being of city-dwellers but our long -term productivity, as well, especially in terms of the quality of life, material and vegetation damage, reduced tourism to the country, discouraged foreign investments, among others. Further, loss of productivity due to pollution-related illnesses becomes a direct economic cost also. Peoples face the greatest health risk due to prolonged exposure to vehicular pollution inevitable in their livelihood. Continued exposure to high levels of common air pollutants such as ozone (O3), oxides of nitrogen (NOx), carbon monoxide (CO) and particulate matter (PM) can result in serious health impacts. In this preliminary study, we analyze the methodological questions raised related with the cost of clean air asset valuation.